Literary relations kinship and the canon, 1660-1830 - Spencer, Jane.; Oxford eBooks (Oxford : Oxford University Press, 2005)
Looking at both real-life relationships between writers and the metaphorical use of kinship terms, this text explores issues in gender theory, as well as recent studies of canon formation.
Description based on print version record.
Includes bibliographical references and index.
Keywords: Kinship; Kinship in literature; Authors, English -- Family relationships; English literature -- History and criticism; English literature -- History and criticism -- Theory, etc; Women and literature -- Great Britain; Influence (Literary, artistic, etc.); Electronic books